The reality of administrative transparency among male and female principals of the intellectual education institutes in Riyadh from the point of view of male and female teachers - Al-Ghmiz, Wafa Turki (Journal of Educational and Psychological Sciences, 2019)
The study aimed to identify the degree of administrative transparency and its impediments among male and female principals of intellectual education institutes in Riyadh and to determine if there were statistically significant differences between the responses of the study sample according to the following variables (gender, qualification, and experience). The study was based on the analytical descriptive approach, and the Questionnaire as a tool. Questionnaire consisted of (48) paragraphs, which were distributed to the study population composed of all the teachers of intellectual education institutes in Riyadh with a total number of 269.The results of the study showed that the degree of practicing administrative transparency among principals of intellectual education institutes in Riyadh is low with an average of (2.57 of 5) and that the obstacles of practicing administrative transparency are very high with an average of 4.32 of 5. The study revealed that there were no statistically significant differences at the level of 0.05 and less in the trends of the study items on the dimensions of administrative transparency according to the following variables (gender, qualification and experience).The study revealed that there were no statistically significant differences in the study items trends regarding the obstacles of administrative transparency according to the variables (experience, qualification) while the results of the study showed that there were statistically significant differences in the study items trends regarding the obstacles of administrative transparency (gender). The test showed differences in favor of male teachers. In the light of the results, the study presents a set of recommendations that emphasize the involvement of both teachers and principals in decision making and proposals.